Petrophysical characterization in paleokarst and effect on reservoir properties - Slotnæs, Katrine Nordlund (The University of Bergen, 2012)
Karst is a geological process that can enhance porosity and permeability within a carbonate succession, thus affecting the heterogeneity producing a substantial effect on the fluid flow. The subject is not widely explored in the petroleum-related literature and hydrocarbon exploration depends on recognizing geological structures. In this case, paleokarst within the Northern Billefjorden, Svalbard, have been used as an analog for classifying paleokarst structures and estimate the petrophysical properties. MAMN-PETR PTEK399